Cognitive and operational implications of non-homogeneous aircraft equipage for aviation system transformation - Pina, Patricia E. (Patricia Elena) (Massachusetts Institute of Technology, 2007)
Thesis (S.M.)--Massachusetts Institute of Technology, Dept. of Aeronautics and Astronautics, September 2007. "August 2007." Includes bibliographical references (leaves 85-87). The air traffic management system is currently experiencing a significant transformation to provide better quality service and to match the increasing air traffic demand. This transformation requires airlines to retrofit their fleet. However, airlines implement new operating capabilities at different rates resulting in long transition periods in which aircraft with different equipage levels coexist in the same airspace. Mixed equipage environments can increase controller workload and task complexity, limit the operational benefits of new operating capabilities, and deteriorate the overall system performance. This study proposes a three dimensional approach to explore mixed equipage effects: (1) understand cognitive implications for controllers, (2) understand operational implications for users, and (3) understand system level implications. To further investigate mixed equipage effects and to illustrate the proposed approach, this study analyzed the implementation of reduced separation standards in the North Atlantic. An experimental analysis was conducted to study the integration of mixed separation standards. Results show significant human factor concerns. Controllers had higher error rates at very low mixed equipage levels. Results also suggest that a contributing causal factor may have been that participants employed inadequate system abstractions based on their current mental models. Airspace segregation based on equipage levels is recommended in the North Atlantic to alleviate controller cognitive limitations and ensure incentives for equipped aircraft. Segregation can facilitate the transition to reduced separation standards. (cont.) A preliminary estimation of the operational benefits that segregation could offer to equipped aircraft in the North Atlantic was performed. We developed a simplified model of the jet stream and ...